New ent-Clerodane and Abietane Diterpenoids from the Roots of Kenyan Croton megalocarpoides Friis & M. G. Gilbert - Ndunda, Beth; Langat, Moses K.; Mulholland, Dulcie A.; Eastman, Harry; Jacob, Melissa R.; Khan, Shabana I.; Walker, Larry A.; Muhammad, Ilias; Kerubo, Leonidah O.; Midiwo, Jacob O. (Planta Medica, 2016)
The roots of the endangered medicinal plant Croton megalocarpoides collected in Kenya were investigated and twenty-two compounds isolated. Among them were twelve new ent-clerodane (1–12) and a new abietane (13) diterpenoids, alongside the known crotocorylifuran (4 a), two known abietane and four known ent-trachylobane diterpenoids, and the triterpenoids, lupeol and acetyl aleurotolic acid. The structures of the compounds were determined using NMR, HRMS and ECD. The isolated compounds were evaluated against a series of microorganisms (fungal and bacteria) and also against Plasmodium falciparum, however no activity was observed.
Keywords: Croton megalocarpoides; Euphorbiaceae; abietane; ent-clerodane; ent-trachylobane; diterpenoids; electronic circular dichroism